Efficiency Of The Legal Role Of Prisoners In The Context Of Guidance At The Class IIB Tanjung Pura Detention Center - Anggi Dian Nugraha; Yasmirah Mandasari Saragih (International Journal of Sociology and Law, 2024)
Inmate development is carried out continuously from the time the inmates enter the correctional institution. The correctional system is a process of developing inmates as creatures of God, individuals and as a society. In coaching inmates, their physical, spiritual and social conditions are developed so that they become reasonable human beings who can live normally in society. The aim of this research is to determine the efficiency of the role of law in coaching at the Class IIB Tanjung Pura Detention Center. This research is included in descriptive research with a type of empirical juridical research using qualitative analysis methods. From the research results, it is known that the implementation of prisoner development is regulated in Law Number 12 of 1995 concerning Corrections, Government Regulation Number 31 of 1999 concerning the Development and Guidance of Prisoners, Government Regulation of the Republic of Indonesia Number 28 of 2006 concerning Amendments to Government Regulation Number 32 of 2006 1999 Concerning Requirements and Procedures for Implementing the Rights of Prisoners, Decree of the Minister of Justice of the Republic of Indonesia Number: M.02-Pk.04.10 of 1990 Concerning the Pattern of Development of Prisoners/Detainees. The implementation of prisoner coaching at the Class IIB Tanjung Pura Detention Center goes through 4 stages, namely the administration or orientation stage, the evaluation stage and determining the type of coaching, the assimilation stage and the integration stage. -existing invitations, planned and programmed work programs in the form of a Strategic Plan, several obstacles were overcome by building a collaborative network with various parties